Upaya Peningkatan Kemampuan Mengenal Konsep Bilangan 1-10 Pada Anak Usia 4-5 Tahun Melalui Permainan Bowling Number Di Pos Paud Dahlia Indah Desa Ginandong - Hermawan, Risdianto; Musyafa Ali; Tiara Amalia (Jurnal Tumbuh Kembang Anak Usia Dini, 2023)
This study aims to improve the ability to recognize numbers in children aged 4-5 years through group A bowling games at the Dahlia Indah Paud Post. This research is classroom action research (classroom actionresseach). The subjects of this study were 1 teacher, 10 children consisting of 5 girls and 5 boys in group A. In collecting the data, researchers carried out documentation and observation techniques. The instruments used are observation sheets, and documentation. The data analysis used is descriptive qualitative. The results of this study show that the use of bowling numbers can improve the ability to recognize the concept of numbers in group A children at the Dahlia Indah Paud Post. Research in cycles I, II and III shows that the ability to recognize the concept of numbers in children can be seen from the results of observations. The ability to recognize the concept of pre-action numbers is 40%, with undeveloped criteria. In the first cycle it reaches 45% with the criteria of starting to develop. The second cycle reached 65% with criteria developing as expected and in the third cycle reaching 82% with very well developed criteria. Thus, it can be concluded that the ability to recognize the concept of numbers in group A children at the Dahlia Indah Preschool Post can be improved through bowling number games.